Medical infrared imaging : principles and practices - Diakides, Mary.; Bronzino, Joseph D., 1937-; Peterson, Donald R. (Donald Russell), 1970- (Boca Raton, Fla. : CRC Press, 2013)
This book explores new ideas, concepts, and technologies such as dynamic thermal imaging, thermal texture mapping, and thermal multispectral imaging commonly used in the clinical environment. The coverage ranges from historical background, concepts, clinical applications, standards, and infrared technology. Of interest to the medical and biomedical engineering communities, the book can provide many opportunities for developing and conducting multidisciplinary research in many areas of medical infrared imaging--Provided by publisher.
1. Advances in medical infrared imaging : an update / Nicholas A. Diakides. [et al.] -- 2. Historical development of thermometry and thermal imaging in medicine / Francis J. Ring and Bryan F. Jones -- 3. Infrared detectors and detector arrays / Paul R. Norton. [et al.] -- 4. Infrared camera characterization / Joseph G. Pellegrino. [et al.] -- 5. Infrared camera and optics for medical applications / Michael W. Grenn. [et al.] -- 6. Physiology of thermal signals / David D. Pascoe, James B. Mercer, and Louis de Weerd -- 7. Quantitative active dynamic thermal IR-imaging and thermal tomography in medical diagnostics / Antoni Nowakowski -- 8. Dynamic thermal assessment / Michael Anbar -- 9. Thermal texture mapping : whole-body infrared imaging and its holistic interpretation / H. Helen Liu and Zhong Qi Liu -- 10. Infrared imaging of the breast : a review / William C. Amalu. [et al.] -- 11. Functional infrared imaging of the breast : historical perspectives, current application, and future considerations / John R. Keyserlingk. [et al.] -- 12. MammoVision (infrared breast thermography) compared to x-ray mammography and ultrasonography : 114 cases evaluated / Reinhold Berz and Claus Schulte-Uebbing -- 13. Detecting breast cancer from thermal infrared images by asymmetry analysis / Hairong Qi, Phani Teja Kuruganti, and Wesley E. Snyder -- 14. Application of nonparametric windows in estimating the mutual information between bilateral breasts in thermograms / M. Etehadtavakol. [et al.] -- 15. Breast cancer screening based on thermal image classification / Boguslaw Wiecek. [et al.] -- 16. Fuzzy C means segmentation and fractal analysis of the benign and malignant breast thermograms / M. Etehadtavakol. [et al.] -- 17. The role of thermal monitoring in cardiosurgery interventions / Antoni Nowakowski, Mariusz Kaczmarek, and Jan Rogowski -- 18. Physiology-based face recognition in the thermal infrared spectrum / Pradeep Buddharaju and Ioannis Pavlidis -- 19. Noninvasive infrared imaging for functional monitoring of disease processes / Moinuddin Hassan. [et al.] -- 20. Biomedical applications of functional infrared imaging / Arcangelo Merla and Gian Luca Romani -- 21. Modeling infrared imaging data for the assessment of functional impairment in thermoregulatory processes / Alessandro Mariotti and Arcangelo Merla -- 22. Infrared thermal imaging standards for human fever detection / Francis J. Ring and E.Y.K. Ng -- 23. Infrared thermal imaging for fever detection in children / Francis J. Ring. [et al.] -- 24. Thermal imager as fever identification tool for infectious diseases outbreak / E.Y.K. Ng -- 25. Thermal imaging in diseases of the skeletal and neuromuscular systems / Francis J. Ring and Kurt Ammer -- 26. Functional infrared imaging in the evaluation of complex regional pain syndrome, type I : current pathophysiological concepts, methodology, case studies, and clinical implications / Timothy D. Conwell and James Giordano -- 27. Thermal imaging in surgery / Paul Campbell and Roderick Thomas -- 28. Thermal signals and cutaneous circulation in physiological research and reconstructive surgery / David D. Pascoe. [et al.] -- 29. Infrared imaging applied to dentistry / Barton M. Gratt -- 30. Laser infrared thermography of biological tissues / Alexander Sviridov and Andrey Kondyurin -- 31. Use of infrared imaging in veterinary medicine / Ram C. Purohit, Tracy A. Turner, and David D. Pascoe -- 32. Standard procedures for infrared imaging in medicine / Kurt Ammer and Francis J. Ring -- 33. Storage and retrieval of medical infrared images / Gerald Schaefer -- 34. Ethical obligations in infrared imaging research and practice / James Giordano and Kim Abramson.
Keywords: Infrared radiation in medicine; Thermography